Analisis Peran Satuan Reserse Narkoba Polres Tuban Dalam Upaya Pencegahan Tindak Pidana Narkotika Di Kabupaten Tuban - Handoko, Teguh Triyo; P (Soetomo Magister Ilmu Administrasi, 2023)
Tuban Regency is one of the areas in East Java which cannot be separated from drug trafficking. Based on the data obtained by the researchers, it shows that since the past two years cases of narcotics trafficking have continued to occur and threaten the lives of the people of Tuban. Therefore the Tuban Police made efforts to prevent the circulation of narcotics from getting bigger in the Tuban district. This research uses descriptive qualitative with the researcher as the key instrument. The focus in this study is how the role of the police apparatus in carrying out efforts to prevent criminal acts of drug abuse. Then what are the influential factors in efforts to prevent narcotics crime. The results of the study show that narcotics in Tuban district are very large and several areas are included in the zone prone to narcotics traffickers. Efforts made by the Tuban Police Narcotics Research Unit include prevention, prosecution and pre-emptive efforts. As a result, the police are able to involve the community to jointly tackle narcotics. Keywords: Concept, Role, Drug Prevention